"As sonoridades de uma catedral que ressoava pelo Pampa": a música na obra do Concerto Campestre, de Assis Brasil - (:unkn) unknown (Universidade Federal do Pampa, 2019)
In the present work, we analyze a work by Rio Grande do Sul writer Luiz Antonio de Assis Brazil, Concerto Campestre (1997), seeking to relate to the theme of music, from a perspective of intertextual analysis comprised between two distinct areas of knowledge: literature and music. Identifies elements of music theory in the construction of narrative, such as the presence of allegro, flat, compasses. An intertextuality presents narrative presents to the reader a figure of the gaucho pampeano, besides the figure of the gaucho woman and all her melancholy, portrayed as a representation of the way of living in the great gaucho resorts of the time of the narrative. To analyze a work, we seek references especially in Werlang (2009), Laham (2008), Sartre (1947), Candido (2006) and Rückert (1997), which do not concern the intertextual relationship of music and literature evidenced in the work.
Keywords: Música; Literatura sul-rio-grandense; Gaúcho; Music; South Rio Grande literature; Gaucho; CNPQ::LINGUISTICA, LETRAS E ARTES